PENGARUH UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Indra Cahya, Kusuma; Gursida, Hari; Indrayono, Yohanes (Jurnal Visionida, 2025)
This study aims to prove whether company size can increase company value and whether profitability can mediate company size in increasing company value. The population of this study is issuers in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for 5 years (2020-2024), totaling 95 companies. The sampling technique used a purposive sampling technique so that from the 95 population, 13 companies can be sampled. Thus, the study used 65 observational data collected in time series. The data analysis technique used Multiple Regression Panel Data with the help of the statistical tool EViews 12 Full Version. The results of this study found evidence that company size directly affects company value and profitability cannot mediate the relationship between company size and company value.